Men of Color Health Awareness intervention: changes in adrenocortical activity assessed using fingernail cortisol - Meyer, Jerrold S.; Markham, Jeffery; Scott, Lamont; Valdez, Luis A.; Robinson, Dean E.; Buchanan, David R. (Frontiers in Public Health, 2025)
IntroductionA randomized controlled trial (#NCT03745703) assessed the efficacy of a tailored stress reduction intervention (Men of Color Health Awareness; MOCHA) aimed at improving the health of middle-aged African-American men. The present paper presents an exploratory study of whether the intervention affected chronic output of the stress hormone cortisol using the novel approach of measuring cortisol accumulation in fingernail samples. Each fingernail sample was hypothesized to contain cortisol deposited over approximately a 3-month period before collection.MethodsSamples were obtained at three time points: prior to beginning of the intervention (T1; which provided an index of cortisol section during a 3-month wait-list control period); at the end of the 10-week intervention (T2); and at 12-week follow-up (T3). Self-reports of perceived stress, depression, and anxiety were collected at the same three time points plus one more: T0, which occurred 12 weeks before T1 and provided baseline psychosocial data.ResultsNail cortisol concentrations were unexpectedly higher at T2 and T3 than at T1, although only the difference at T2 reached statistical significance. Nail cortisol was not associated with any self-reported psychosocial measure at any time point.DiscussionThe nail cortisol data suggest that long-term life stressors experienced by the participants may have led to a suppression of adrenal cortisol release, which was at least transiently ameliorated by the MOCHA intervention. The lack of any apparent relationships between cortisol levels and measures of perceived stress, depression, or anxiety is consistent with prior findings that endocrine responses to stress often fail to covary with subjective responses to the same stress.